ANTIBACTERIAL ACTIVITY OF ETHANOL EXTRACT OF EDAMAME PEEL AND SEEDS (Glycine max (L.) Merr) AGAINST THE GROWTH OF Staphylococcus aureus - Rahmadaniah Affelia; aliyah purwanti; Dhina Susanti (Indonesian Pharmacopeia Journal, 2024)
Staphylococcus aureus is the cause of acne disease that is resistant to antibiotics in the long term. Edamame is one of the natural ingredients used as an alternative treatment. Edamame seeds have the potential as antibacterial because they contain saponin compounds, in addition edamame peel waste can also be developed as an antibactetrial. The study aims to identify the profile of compound content from edamame peel and seeds extracts, to identify and analyze the antibacterial activity of the extract against Staphylococcus aureus bacteria. Ethanol extract of edamame peel and seeds were obtained from the Ultrasonic Assisted Extraction (UAE) method using 96% ethanol. Each extract was screened for phytochemicals and than made into concentrations of 10%, 20% and 30% to test antibacterial activity using the well diffusion method. Then continued with the One Way Anova test. Ethanol extracts of edamame peel and seeds obtained an average yield of 17,31%±0,57 and 17,10%±0,51. Edamame peel and seeds extracts contain saponins, tannins, steroids, terpenoids, flavonoids dan phenols but edamame seeds do not contain steroid compounds. Edamame peel extract at concentration of 10%, 20% and 30% can inhibit Staphylococcus aureus with an average inhibition zone diameter of 10,13mm±0,54; 12,80mm±0,67 and 14,74mm±0,78 while ethanol extract of edamame seeds produces an average inhibition zone diameter of 9,32mm±0,67; 11,55mm±0,83 and 13,83mm±0,96. The one way Anova test produced a value (Sig.) 0,000 followed by the Post Hoc LSD test showing that there were significant differences between each group. Edamame peel and seeds extracts contain phytochemical compounds such as flavonoids,steroids, phenols, tannins, terpenoidsa and saponins where each compound has a mechanism of inhibiting the growth of Staphylococcus aureus. The antibacterial activity of edamame peel extract is classified as strong at each concentration, while edamame seed extract is classified as strong at concentration of 20% and 30%, than at the concentration of 10% it is classified as moderate.